2020
DOI: 10.1097/md.0000000000022472
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic compression for anastomosis in treating an infant born with long-gap oesophageal atresia

Abstract: Rationale: Neonatal long-gap esophageal atresia (LGEA) with tracheoesophageal fistula (TEF) is an uncommon but serious congenital malformation of the esophagus in newborns, and it remains challenging for pediatric surgeons. Magnetic compress has been shown to be effective for the treatment of LGEA in children and adults. However, the implementation of this unique technique for neonatal LGEA has not been evaluated. Patient concerns: A female infant was born at 37 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Unfortunately, this procedure was associated with a high number of anastomotic strictures requiring repetitive dilatations [ 8 ]. Since then, a small number of case reports and case series have been published using these original, and other, magnets [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this procedure was associated with a high number of anastomotic strictures requiring repetitive dilatations [ 8 ]. Since then, a small number of case reports and case series have been published using these original, and other, magnets [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One clinical report showed that anastomosis was achieved in an average of 6 d (range 3 to 7 d) in 5 patients (age 6 mo to 5.9 years) with severe recurrent postsurgical esophageal stenosis refractory to dilatation[ 25 ]. Another MCA was achieved on day 36[ 26 ]. Clinical reports have shown that the anastomosis time ranges from 3 d to 36 d[ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another MCA was achieved on day 36[ 26 ]. Clinical reports have shown that the anastomosis time ranges from 3 d to 36 d[ 26 - 28 ]. It involves many factors, such as the age of the child, type of EA, size of the magnetic ring and field strength of the magnetic device.…”
Section: Discussionmentioning
confidence: 99%
“…MCA has been used for minimally invasive cardiac bypass surgery[ 9 , 10 ] and for the treatment of biliary obstruction after liver transplantation[ 5 , 11 - 13 ]. In recent years, in addition to the application of MCA in gastrointestinal anastomosis[ 14 - 17 ], rectum atresia, and colorectal stricture in children[ 4 , 16 , 18 , 19 ], more clinical studies have been reported on its application in refractory stricture after esophageal atresia (EA). Zaritzky et al [ 18 ] showed that MCA achieved esophageal reanastomosis within 6 d in infants with EA who had primary or secondary anastomotic stenosis.…”
Section: Discussionmentioning
confidence: 99%